Maternal Variables Influencing Duration of Breastfeeding Among Low-Income Mothers - McKechnie, Anne Chevalier (2009)
This study used a retrospective comparison of 2 naturally occurring groups, first to examine how exclusive versus partial breastfeeding relates to duration of breastfeeding and, second, to determine if factors such as age and body mass index are associated with exclusive versus partial breastfeeding duration. These factors were hypothesized to influence the amount of breastfeeding in a sample of 42 low-income mothers enrolled in the Supplemental Nutrition Program for Women, Infants, and Children of a predominately rural, Midwestern county. This study examined de-identified data from a state database spanning a calendar year. Breastfeeding behavior, age, and body mass index measurements for mothers giving birth within the first 6 months of that year were analyzed. Exclusive breastfeeding mothers breastfed longer, were of older age, and had lower body mass indexes than partial breastfeeding mothers. These findings further describe characteristics of low-income breastfeeding women. Understanding how factors associated with exclusive versus partial breastfeeding affect breastfeeding duration may inform clinicians and researchers of areas for future interventions.